MEASUREMENT OF THE PROTON STRUCTURE-FUNCTION F2 IN EP SCATTERING AT HERA - Derrick, M; Krakauer, D; Magill, S; Musgrave, B; Repond, J; Repond, S; Stanek, R; Talaga, R; Thron, J; Arzarello, F; Ayad, R; Bari, G; et al. (1993)
This paper presents our first measurement of the F2 structure function in neutral-current, deep inelastic scattering using the ZEUS detector at HERA, the ep colliding beam facility at DESY. The data correspond to an integrated luminosity of 24.7 nb-1. Results are presented for data in a range of Q2 from 10 GeV2 to 4700 GeV2 and Bjorken x down to 3.0 x 10-4. The F2 structure function increases rapidly as x decreases.